Training on the Production of Organic Compost Fertilizer from Mushroom Baglog Waste - Riesnawa, Yurdien Dellan; Setiyawan, Hendhi; Rizky, Miftakhul; Fadilah, Nurul; Chairil, Augustin Mustika (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: Organic waste from oyster mushroom cultivation bags in Gayungan Village, RW 03, has long been underutilized. The purpose of making compost from oyster mushroom cultivation bag waste is to improve the community's knowledge and skills in sustainable waste management. Method: The training was conducted through socialization, question and answer sessions, and mentoring, involving 25 participants. The approach used was as follows: quantitative data was collected through pre- and post-training evaluations, while qualitative insights were obtained from interviews and field observations. The data was analyzed using descriptive statistics and thematic analysis. Practical Applications: This training effectively improves participants' knowledge and skills in processing mushroom baglog waste into organic fertilizer. This raises public awareness, reduces waste accumulation, and encourages environmentally friendly agricultural practices. Some residents have implemented composting techniques independently, demonstrating the potential for small-scale economic development. This program supports sustainable waste management and community empowerment. Conclusion: This program demonstrates that targeted environmental education combined with hands-on practice can foster behavioral change, promote circular economy principles, and enhance community resilience through sustainable agriculture.